2019
DOI: 10.1016/j.envres.2019.108549
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of prenatal exposure to fine particulate matter (PM2.5) and ozone (O3) on the risk of preterm birth: A population-based cohort study

Abstract: BACKGROUND:There is some evidence that prenatal exposure to low-level air pollution increases the risk of preterm birth (PTB), but little is known about synergistic effects of different pollutants. OBJECTIVES:We assessed the independent and joint effects of prenatal exposure to air pollution during the entire duration of pregnancy. METHODS:The study population consisted of the 2,568 members of the Espoo Cohort Study, born between 1984 and 1990, and living in the City of Espoo, Finland. We assessed individual-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 51 publications
(53 reference statements)
5
55
0
Order By: Relevance
“…Our results strengthen the evidence of independent effects of CO and O3 exposures on the risk of LBW. Our study shows, for the first time, synergistic effects of air pollutants on fetal growth, which is in line with synergistic effects on the risk of preterm birth which we presented recently [15]. Our results also indicate presence of season-specific effects.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results strengthen the evidence of independent effects of CO and O3 exposures on the risk of LBW. Our study shows, for the first time, synergistic effects of air pollutants on fetal growth, which is in line with synergistic effects on the risk of preterm birth which we presented recently [15]. Our results also indicate presence of season-specific effects.…”
Section: Discussionsupporting
confidence: 91%
“…We found that high levels of PM2.5 and O3 exposure during entire pregnancy increase the risk of LBW synergistically with an excess risk of 144% above the additive effect. This result is consistent with our previous study on air pollution and PTB [15] where a 152% excess risk was found in relation to PTB. To the best of our knowledge, ours is the first study to estimate the joint effect of air pollutants on the risk of low birth weight.…”
Section: Synthesis With Previous Knowledgesupporting
confidence: 93%
See 2 more Smart Citations
“…Exposure to both PM and O 3 has been associated with a higher risk of preterm birth [91, 92, 94, 95]. Synergies between PM2.5 and O 3 showed worse outcomes (risk ratio = 3.63) than their independent effects (risk ratio = 0.99 and 1.34, respectively) [96]. Moreover, the multicentre European birth cohort HELIX study with 1,396 subjects showed that prenatal and first year of childhood exposure to NO 2 and PM2.5 were inversely associated with telomere length [97].…”
Section: Environmental Exposure During Pregnancymentioning
confidence: 99%